(3CMcGe YbO GdMSGH GdLGQj aj bGfhf GdJLGQI GdLOjO (B/s - (3LeYI, CMeO eMehOs ((3GdGScfOQjI(B: s (3efTCI GdeYGQa(B, s, 2003)
(3bGYOI YOe JLRFI GdeaQOGJ GdebjOI aj GdMSGH GdLGQj gj GdQcjRI GdCSGSjI GdJj Jbhe YdjgG CMcGe YbO GdMSGH GdLGQj aj bGfhf GdJLGQI GdLOjO Qbe (B17 (3dSfI (B1999(3,bGYOI GdCKQ GdJLOjOj ddMbhb GdJj JbjOHGdMSGH GdLGQj,QaV GdeTQY dfXQjI GdebGUI GdeJJGHYI aj bGfhf GdJLGQI GdLOjO,fXQjI YOe JLRFI eaQOGJ GdMSGH GdLGQj,JWHjbGJ eHOCYOe JLRFI eaQOGJ GdMSGH GdLGQj,YOe LhGR GdJeSc HGdbGUI Hjf eaQOGJ GdMSGH GdLGQj CKfGA JTZjdg,YOe LhGR eWGdHI CMO WQaj GdMSGH GdLGQj GdWQa GdBNQ HbjeI CMO eaQOGJ GdMSGH,YOe LhGR SMH ChQGb JLGQjI Ydi eaQOGJ GdMSGH GdLGQj,GdMLR Ydi GdQUjO GdeDbJ ddMSGH GdLGQj(B- (3JMOjO fWGb JWHjb bGYOI GdNWQ,GdGSJKfGAGJ GdhGQOI Ydi bGYOI GdNWQ,GdeSDhdjI GdeOfjI hGdLfGFjI Yf eNGdaI GdNWQ HJUMjM GdMSGH GdLGQjs
(3HHdjhZQGajG U(B.204s
Keywords: (3GdMSGH GdLGQjs; (3GdbGfhf GdJLGQjs; (3JLGQIs